Atrial Cardiomyopathy Predicts Worse Outcome in Patients With Lung Cancer - Ren, Mengdi; Ma, Yuyan; Wei, Meng; Ning, Yuye; Liu, Hui; Shi, Xue; Yao, Yu; Guo, Fengwei (Frontiers in Cardiovascular Medicine, 2022)
Background Reports of the clinical outcomes associated with the co-occurrence of atrial cardiomyopathy (ACM) and lung cancer (LC) are limited. Objectives This study aims to investigate the influence of ACM on the prognosis of LC patients and related clinical determinants. Methods Newly diagnosed LC patients from January 1st, 2015, to December 31st, 2020, were retrospectively enrolled at the First Affiliated Hospital of Xi’an Jiaotong University. The demographics and overall survival (OS) of the patients with or without ACM were compared. The survival rate was analyzed using the Kaplan–Meier method and multivariate Cox regression analysis. Binary logistic regression analysis was used to determine the risk factors for ACM. Results A total of 306 patients (65.04 ± 10.30 years of age, 72.88% male) were analyzed. The prevalence of ACM in the non-small cell lung cancer (241, 78.76%) and small cell lung cancer (65, 21.24%) population was not statistically different. Overall, 53 (17.32%) LC patients had coexisting ACM. ACM patients were older (69 vs. 64, p = 0.0013) and had higher D-dimer levels (1.0 vs. 0.6, p = 0.001), lower serum calcium levels (2.23 vs. 2.31, p = 0.001), lower left ventricular ejection fraction (LVEF) values (67% vs. 69%, p = 0.036) and had more frequent coronary comorbidity disease (16.98% vs. 8.82%, p = 0.031). The median OS for patients with or without ACM was 15 months and 25 months, respectively (p = 0.018). Coexisting ACM compared to non-ACM was associated with worse OS in patients with LC (HR = 1.543, 95% CI: 1.042–2.283, p = 0.030). Conclusion Coexisting ACM is associated with undesirable survival outcomes in patients with LC. These findings could help us to better understand the cardiac burden in these patients and provide additional risk stratification for them.